If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + 7v = 13v Solving 36 + 7v = 13v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-13v' to each side of the equation. 36 + 7v + -13v = 13v + -13v Combine like terms: 7v + -13v = -6v 36 + -6v = 13v + -13v Combine like terms: 13v + -13v = 0 36 + -6v = 0 Add '-36' to each side of the equation. 36 + -36 + -6v = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -6v = 0 + -36 -6v = 0 + -36 Combine like terms: 0 + -36 = -36 -6v = -36 Divide each side by '-6'. v = 6 Simplifying v = 6
| 10x-5y+6=6 | | 3(1+6m)=-16-m | | 0.03-0.4x=1.85 | | 7-3(9-x)=16 | | 2(a+6)=5+9 | | 3n^3+10n+16=8 | | 2z^2+5z+3= | | 2b+8(2b-3)=-3(-5b-6) | | -n-21=3(6n-7) | | -2x+19+5x-11=x | | 16+7yi=-8x+i | | 2x-2=x^2-5 | | 4(x+4)=4(x-2) | | 3x-7=3x+1-1 | | 2z^2+9z+10= | | 9x^3-3x^2-3x+7=0 | | 0.9=2.176 | | (5+9i)2= | | -3x(x-4)+15=-5(x-7)-10 | | 6-7x=5x-8+10 | | 2x+3-x^2-5= | | 4x+4=-8+2x+20 | | -4(2x-6)=33 | | 5x+7=15x-1 | | 2t^2+7t+5= | | m/19=56/133 | | x^4=0.7 | | x^4=7 | | 2u^2-11u+12= | | 2(y+3)=4(y+2) | | -3(2x-7)=28 | | 0.8-2x=(-3x) |